English to GCSE - Barton, Geoff (Ney York : Oxford University, 1996)
Encourages students to read texts at deeper levels and develop their own writing style. This book contains features such as clear objectives, practical activities, follow-up activities, examples, and comments and advice from an experienced GCSE examiner, that helps students look critically at others' writing and then at their own.
Keywords: English literature Examinations; English language Examinations, questions; English language